1995
DOI: 10.4319/lo.1995.40.3.0575
|View full text |Cite
|
Sign up to set email alerts
|

Continuous measurement of CO2 for estimation of air‐water fluxes in lakes: An in situ technique

Abstract: Three parameters must be known to use the thin boundary-layer model (or other bulk transfer models) for CO, flux between water and air: the concentration of dissolved CO*, CO,,,,,, the concentration of CO, in the air immediately above the water, COZ(atm), and the wind velocity, which is used to determine the appropriate transfer coefficient. These parameters change hourly and from day to day in a nonlinear fashion, so the frequency of measurements is an important factor in determining the accuracy of flux esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 10 publications
(11 reference statements)
1
33
0
1
Order By: Relevance
“…Sellers et al, 1995;Cole and Caraco, 1998;Hanson et al, 2006) but generally showed small variation. Cole and Caraco (1998) for instance, recorded small CO 2 changes within a day in midsummer and even smaller ones during the spring in Mirror Lake.…”
Section: Discussionmentioning
confidence: 99%
“…Sellers et al, 1995;Cole and Caraco, 1998;Hanson et al, 2006) but generally showed small variation. Cole and Caraco (1998) for instance, recorded small CO 2 changes within a day in midsummer and even smaller ones during the spring in Mirror Lake.…”
Section: Discussionmentioning
confidence: 99%
“…We did not face biofouling problems, but in longer measuring campaigns, the silicone rubber tubing must be cleaned or replaced regularly in order to avoid decrease in gas diffusion. The CO 2 concentration dynamics with a peak during morning and minimum near dusk resembled that recorded by Sellers et al (1995) with a more costly system of in situ equilibrium chamber (ISEC) connected to IRGA in August 1992 in Lake 979 at the Experimental Lakes Area (ELA). Our diel cycle in CO 2 concentration is also very similar to that measured by Hanson et al (2003) in mid-July in the mesotrophic Cranberry lake using a Li-Cor IRGA.…”
Section: Discussion Comments and Recommendationsmentioning
confidence: 90%
“…In a study by Sellers et al (1995), higher CO2 concentrations were recorded around 09:00, followed by lower values around 20:00 and it was demonstrated that more frequent sampling is necessary. Diel changes in CO2 concentration was reported in a Finnish lake and the importance of accounting for diel changes has been emphasized in a study by Huotari et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…and CO2 fluxes (Mattson and Likens 1990;Hamilton et al 1994;Sellers et al 1995;Bastviken et al 2004Bastviken et al , 2010Huotari et al 2009). Additional studies of variability between days-weeks would be very valuable to understand and predict how rapidly fluctuating environmental variables affect GHG fluxes from inland waters (beyond the connection between air pressure changes and CH4 ebullition; e.g.…”
Section: Introductionmentioning
confidence: 99%